The Influence of the 'Earth Tells' Module Based on Ethnomathematics on the Mathematical Literacy Skills of Fifth Grade Elementary School Students - Pohan, Rinanti Ito; Wandini, Rora Rizky (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The low level of mathematical literacy among elementary school students in Indonesia has become a significant problem in education, as mathematical literacy encompasses not only arithmetic skills but also logical thinking, problem-solving, and the application of mathematical concepts in everyday life. This research aims to examine the effect of using the ethnomathematics-based module 'Bumi Bercerita' on the mathematical literacy skills of fifth-grade elementary school students. A quasi-experimental method with a Nonequivalent Control Group Design was used, involving 55 fifth-grade students at SDN 106161 Laut Dendang, with 28 students in the experimental group and 27 in the control group. Data were analyzed using an independent sample t-test. The analysis results show a significance value of 0.007 (p < 0.05), indicating a statistically significant difference between the mathematical literacy outcomes of students in the experimental class and the control class. Therefore, the ethnomathematics-based module has been proven to be more effective in enhancing students' ability to formulate problems, apply concepts, interpret results, and evaluate solutions, as well as in fostering a more positive attitude towards learning mathematics.